Simulium (Thyrsopelma) duodenicornium, a new black fly species (Diptera: Simuliidae) from the Southeast Region of Brazil - Pepinelli, Mateus; Hamada, Neusa; Trivinho-Strixino, Susana (Zootaxa, 2005)
We describe the female, male, pupa, and larva of a new black fly species in the subgenus Thyrsopelma. Males of Simulium duodenicornium n. sp. have a black scutum, without silver bands or patterns, covered with golden yellow hairs. The female scutal pattern is similar to that of most other species in the subgenus Thyrsopelma with a black scutum covered by groups of gray-whitish hairs. Males of the new species can be distinguished by the shape of the ventral plate and females by the shape of the hypogynial valves. The pupa of the new species has 12 short, thick, rigid gill filaments, with highly sclerotized and pointed tips. The pupa is similar to those of Simulium guianense s. l. Wise and Simulium perplexum Shelley, Maia-Herzog, Luna Dias & Couch, but the gill filaments are thicker basally and do not have spicules in an annular arrangement. The larvae are similar to those of most species in the subgenus Thyrsopelma, with ovoid setae covering the body cuticle. The stream in which S. duodenicornium was collected forms part of the headwaters of the Piracicaba River, which is a tributary of the Tietê River. This stream is located in Joanópolis County, São Paulo State, Brazil, in a rainforest area of the Serra da Mantiqueira, in the Atlantic Forest (Mata Atlântica) domain.